Epiphytic Diatoms in Environmental Bioindication: A Case Study of a Significant Natural Lake in the Northwest of Türkiye - Cem Tokatlı; Cüneyd Nadir Solak; Abu Reza Towfiqul Islam; Ahmet Miraç Titiz; Elif Yılmaz; Tahir Atıcı (Acta Scientiarum Polonorum. Formatio Circumiectus)
Aim of the study: The Gala Lake, which has a status of National Park and is an under-protection area, is the one of the most important natural stagnant water bodies in the Marmara Region of Türkiye. However, it is under effect of a significant agricultural stress sourced by mainly paddy cultivation. In this research, the epiphytic diatoms of Gala Lake were investigated, and the trophic status of the lake was assessed by applying the Biological Diatom Index (BDI).